The Difference between the Effect of Green Tea Cream and Tocopherol on Decreasing Level of Tyrosinase Enzyme and Amount of Melanin in Rattus norvegicus Exposed to UVB Rays - Riyanto, Anwar; Nasihun, Taufiqurrachman; Sumarawati, Titiek (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction: Green tea and tocopherol are potent antioxidants used to treat melasma. However, whether green tea or tocopherol is superior remains unclear. Objective: To compare the effectiveness between green tea and tocopherol in decreasing the amount of melanin and tyrosinase level in wistar rats exposed to UVB rays.Methods: The experimental study took 30 male Wistar rats randomly and divided them into 3 groups. The control group (C-G) was given basic topical cream, GT-G was given green tea topical cream and TC-G was given tocopherol topical cream. All rats were exposed to UVB every Monday, Wednesday and Friday for 4 weeks, whereas topical creams were smeared every day. Topical creams smearing on the same day with UVB exposure was performed 20 minutes before exposure and 4 hours after UVB exposure. The doses of UVB were 50 mJ/cm2 in first week, 70mJ/cm2 in the second week and 80mJ/cm2 in the third and fourth weeks. The amount of melanin was measured using pixel method and the tyrosinase level was measured using ELISA.Results: Anova analysis indicates that the amount of melanin and tyrosinase level are significantly different between groups, p<0.05. Post Hoc LSD analysis indicates that the amount of melanin in GT-G and TC-G are significantly lower than that of C-G, p<0.05. The amount of melanin in GT-G is lower than that of TC-G, p<0.05. The tyrosinase level in GT-G is significantly lower than that of C-G and TC-G, p<0.05. Meanwhile, the tyrosinase level in TC-G is lower than that of C-G but insignificantly, p>0.05.Â  Conclusion: Green tea topical treatment is significantly capable of decreasing the amount of melanin and tyrosinase level better than tocopherol.